Instructional Design Model for Applying Flipped Learning in Higher Education Institutions - Eltahir, Mohd Elmagzoub A. Babiker (European Journal of Social Science Education and Research, 2018)
The era of globalization, growth and development of information and communication technology (ICT) and its application to learning and teaching has influence on our modern generation students, making the teaching traditional methods are useless. Changing familiar instructing methods can be a challenge available for instructors as a way to ignite our students’ curiosity and make our teaching materials more engaging and effective. Recently, the flipped learning model has been recognized by educators as an effective instructional approach (Hwang, - Wang 2015), it is a pedagogical approach in which the typical lecture and activities elements of a course are reversed, where students individually watch online lectures prior to class and then engage in classroom learning activities interacting with peers and instructors. Flipped learning model helps instructor to focus more on student-centered learning, which includes any use of the technology to take advantage of learning in the classroom, so that the instructor can spend more time interacting with the students instead of lecturing. The purpose of this study is to suggest instructional design (ID) model for teaching undergraduate courses applying the flipped learning model. Research on ID models may be classi?ed into three different types: model development, model validation, and model use. This study concerned the ?rst one of these, and it is based on the ADDIE, Dick and Carey model. The process begins with planning, followed by programming, then Coaching. Assessing and evaluating occur continually throughout the process and act as valuable mechanisms for monitoring progress and identifying achievement. At each stage of the process, instructors base their decisions on the requirements of the course curriculum, and, equally importantly, on their students’ needs.
Keywords: Flipped Learning, Flipped Classroom, Flipped Pillars, Information Communication Technology (ICT), Instructional Design (ID).